1997
DOI: 10.1074/jbc.272.40.25062
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Raf-1 Induces the Expression of Non-histone Chromosomal Architectural Protein HMGI-C via a p44/p42 Mitogen-activated Protein Kinase-dependent Pathway in Salivary Epithelial Cells

Abstract: The enzyme activity of mitogen-activated protein kinase (MAP kinase) increases in response to agents acting on a variety of cell surface receptors, including receptors linked to heterotrimeric G proteins. In this report, we demonstrated that Raf-1 protein kinase activity in the mouse parotid glands was induced by chronic isoproterenol administration in whole animals. To investigate the molecular nature underlying cellular responses to Raf-1 activation, we have stably transfected rat salivary epithelial Pa-4 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 63 publications
(62 reference statements)
2
39
0
Order By: Relevance
“…ing the modulation of ␣-ENaC mRNA level (11,30). In this context, a partial aim of the present study was to identify the regulatory elements of the rat ␣-ENaC gene responsible for Raf/ERK-mediated down-regulation of ␣-ENaC expression in salivary epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…ing the modulation of ␣-ENaC mRNA level (11,30). In this context, a partial aim of the present study was to identify the regulatory elements of the rat ␣-ENaC gene responsible for Raf/ERK-mediated down-regulation of ␣-ENaC expression in salivary epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 20 g of whole cell extract from each sample was subjected to a 10% SDS-polyacrylamide gel electrophoresis. The immunoblot analyses were carried out as described previously (23). The anti-PY-STAT and anti-STAT antibodies used were purchased from New England Biolabs (Beverly, MA) and Transduction Laboratories (Lexington, KY), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…We had previous success in using the conditionally active Raf-1, ⌬Raf-1:ER, which was engineered by fusing the kinase domain of Raf-1 with the HBD of human ER, in our studies to characterize the biological function mediated by the Raf-1 kinase activation in epithelial cells (23,28). A similar approach was employed to construct a conditionally active Etk for our current studies.…”
Section: Construction Of Conditionallymentioning
confidence: 99%
“…Previous studies by us and other groups have shown that aberrant expression of architectural transcription factor HMGA2 is associated with the regulation of cell proliferation and gene expression (8,19,20,23,24). We therefore sought to screen for novel HMGA2-interacting proteins that mediate the pleiotropic effects by HMGA2.…”
Section: Hmga2 Is Sumoylated In Vitro and In Vivomentioning
confidence: 99%
“…The rat parotid epithelial cell line Pa-4, also known as parotid C5 cells, was plated on Primaria culture dishes (Falcon) in DMEM/Ham's F-12 (1:1) medium supplemented with 2.5% FCS, insulin (5 Ag/mL), transferrin (5 Ag/mL), epidermal growth factor (25 ng/mL), hydrocortisone (1.1 Amol/L), glutamine (5 mmol/L), and kanamycin monosulfate (60 Ag/mL) and maintained in a humidified atmosphere of 5% CO 2 , 95% air at 35jC (19). The HeLa/HMGA2 cells were established by stably transfecting HeLa cells with pcDNA3.1-HA-HMGA2, followed by a selection with G418 (1000 Ag/mL).…”
Section: Cell Culturementioning
confidence: 99%